Percepções geométricas: as dificuldades na aprendizagem da geometria - PINHEIRO, Giselle Feio (2019)
The present work objective present the difficulties encountered by students in several stages of the teaching of geometry learning. In this context, we observe that difficulties of perception and geometric visualization that arise due to defict in the application of its fundamental concepts. Therefore, it is necessary to investigate and develop new methodological strategies that simplify the understanding of the basic concepts of geometry. Thus, the work developed from bibliographical research and methodological application in the classroom to identify the main needs. Thus, generate a reflection around current teaching practices and collaborate on the problem of the application of geometry.